Implementation of innovative technologies as the basis for the effective functioning of hospitality industry enterprises (Economics and region, 2024)
Implementation of innovative technologies as the basis for the effective functioning of hospitality industry enterprises. The article analyzes the implementation of innovative technologies "open key" and "smart room" at hospitality industry enterprises, and examines their impact on the quality of service, competitiveness and operational efficiency of hotels. The main advantages of these technologies are identified: increasing the level of security and personalization of guest experience, optimizing energy consumption, reducing maintenance costs and simplifying resource management. It is proven that innovations such as "open key" and "smart room" allow hotels to meet modern customer needs and contribute to the sustainable development of the hospitality industry. The key aspects and advantages of open key and smart room technologies are considered, their role in improving the quality of service and increasing security, as well as their potential in reducing the environmental burden and expanding the possibilities of a personalized approach to each guest. The introduction of innovative technologies such as open key and smart room in hospitality industry enterprises is an important step to improve the quality of services, optimize resources and increase the competitiveness of establishments. As a result of adapting these technologies, hotels can provide guests with a comfortable and safe experience that meets the modern expectations of travelers. Mobile keys, accessible via smartphones, allow guests to access rooms without traditional registration, which not only saves time, but also reduces the need for physical contact, which is especially important in conditions of increased security requirements. The smart room system, in turn, gives guests control over their stay, allowing them to adjust lighting, temperature, multimedia and even order additional services using a mobile application. This significantly improves the guest experience, and for the hotel, it means reduced energy costs and more efficient resource management.
Keywords: innovative technologies; open key; smart room; hotel business; service quality; competitiveness; automation; optimization of energy consumption; personalization